Fatal necrotic tracheitis by Aviadenovirus in captive Alagoas curassows (Pauxi mitu) extinct from the wild. Issue 3 (4th May 2019) - Marques, Marcus Vinicius Romero; Marin, Sandra Yuliet; Couto, Rodrigo de Macedo; Ecco, Roselene; Resende, Mauricio; Martins, Nelson Rodrigo da Silva
ABSTRACT: Extinct from nature, captive young Alagoas curassows ( Pauxi mitu ) were found agonizing or dead with respiratory disease. Intranuclear inclusion bodies were found in the epithelia of the trachea, associated with marked necrotic tracheitis. An Aviadenovirus was isolated in chicken eggs and characterized genetically with 99% identity to the fowl Aviadenovirus A, as based on the hexon protein gene. This is the first report of respiratory disease caused by Aviadenovirus in any cracid species in Brazil, recommending for stricter biosecurity in the conservation premises. RESEARCH HIGHLIGHTS Fatal tracheitis in curassows extinct from nature was associated with Aviadenovirus A. Seven-month-old Alagoas curassows (Aves: Cracidae) died with haemorrhagic tracheitis. Aviadenovirus A with 99% identity to fowl adenovirus 1 was detected in dead curassows. Fatal tracheitis by Aviadenovirus was described in Pauxi mitu (Aves: Cracidae).